Pengenalan Lapangan Persekolahan pada Mahasiswa di SMKN 6 Pekanbaru - Alviana Khairiah Nasution; Khairul Anshari (Lembaga Pengembangan Kinerja Dosen, 2025)
Introduction to School Field (PLP) is an academic program designed to provide students with direct experience in the world of education. This program aims to enable students to understand the real situation in schools, improve their teaching skills, and hone their professional abilities as prospective educators. In the implementation of PLP at SMKN 6 Pekanbaru, four students participated in this activity from January 13 to February 22, 2025. They were given the opportunity to teach English to students in grades 10 (RPL 1 & 2), 10 (TE 1 & 2), and 11 (MEKA 1 & 2). Through this program, students can gain valuable experience in managing classes, compiling learning tools, and interacting directly with students and educators. In addition, the PLP program also provides benefits for schools in improving the quality of learning. This article will discuss the implementation of PLP in detail, starting from the methods used, the results obtained, to the benefits felt by students and learners.